Antimicrobial Polyethylene through Melt Compounding with Quaternary Ammonium Salts. (30th April 2017) - Rossetti, Fernanda F.; Siegmann, Konstantin; Köser, Joachim; Wegner, Irene; Keskin, Ismail; Schlotterbeck, Götz; Winkler, Martin
Abstract : Selected mono- and bicationic quats were compounded with polyethylene. The physicochemical surface properties, leaching behavior, and antibacterial activity of such modified samples were investigated. Contact angle measurements and fluorescein binding assays showed the presence of quaternary ammonium groups at the surface. After storing the samples in 50°C warm water for 30 days, several were still antimicrobially active. No correlation between the number of exposed N + head groups after leaching and the antibacterial activity was observed. There is however a qualitative correlation of the antibacterial activity with the contact angles and surface concentrations of N + before leaching/storing in warm water.